2015
DOI: 10.1007/978-3-319-21067-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual, Augmented and Mixed Reality

Abstract: Abstract. We here describe a novel approach for locally obtaining pose estimation of match feature points, observed using RGB-D cameras, in order to apply to locally planar object pose estimation with RANSAC method for augmented reality systems. Conventionally, object pose estimation based on RGB-D cameras are achieved by the correlation between observed 3D points captured by feature point matching and known 3D points of the object. However, in such methods, features are simplified as single 3D points, losing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…Table 2 shows the results for the risk of bias assessment. All the studies included in this review reported the sampling method [41][42][43][44][45][46][47][48][49][50][51], although the performance and the detection biases during blinding phase were unclear for all but one [41]. Concerning the outcomes, only two studies [45,47] presented high risk of bias for missing data handled appropriately or for missing a match between methods and results.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 2 shows the results for the risk of bias assessment. All the studies included in this review reported the sampling method [41][42][43][44][45][46][47][48][49][50][51], although the performance and the detection biases during blinding phase were unclear for all but one [41]. Concerning the outcomes, only two studies [45,47] presented high risk of bias for missing data handled appropriately or for missing a match between methods and results.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Two of these used Mindfulness-based Stress Reduction (MBSR) Meditation through virtual environments as a non-pharmacological approach to treating chronic disorders, such as chronic pain [43], and patients with traumatic brain injuries [44]. In both studies, virtual meditation was significantly more effective than MBSR alone in reducing reported levels of pain [43], and at making participants experience a higher level of satisfaction [44]. Singh et al have examined the impact of VR games on psychological wellbeing, upper limb motor function and reaction time in adults with physical disabilities.…”
Section: Virtual Environments For Patientsmentioning
confidence: 99%
See 3 more Smart Citations